Wykorzystanie controllingu i rachunkowości zarządczej do poprawy gospodarności przedsiębiorstw branży spożywczej i mięsnej - Dynowska, Joanna; Łapińska, Anna (The Usage of Controlling and Management Accounting for Improving the Efficiency of Firms of Food and Meat Branch, 2005)
The system of controlling and management accounting does not solve directly all problems appearing in a firm but it reveals them. Due to the better awareness of costs it is possible to reduce them. The application of some controlling instruments in the analysed firms of food and meat branch enabled most of them to realise their aims and lower their costs. It also improved the cooperation between departments within the firms as well as the information flow, thus making the firms more efficient and competitive on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 178-185